Slavery's Borderland : Freedom and Bondage Along the Ohio River - Salafia, Matthew (Book collections on Project MUSE., 2013)
By centering the practical and figurative significance of the Ohio River as a political border, a cultural boundary, and an artery of movement and economy that gave form to the region, the author sheds light on peculiarities of labor and economy along the Ohio River.